HUBUNGAN SOSIAL PRODUKSI PADA INDUSTRI RUMAH TANGGA GULA MERAH DI KENAGARIAN TANJUANG BUNGO KECAMATAN SULIKI KABUPATEN LIMA PULUH KOTA. - Rival Arsyad; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study was conducted in the village of Tanjuang Bungo, Suliki District, district fifty cities West Sumatra. The goal is to know the social relationship of production between toke and Labour in the red sugar industry and knowing the social connections fulfill the patron's patrons ' relationship. Sample writing techniques purposive sampling in determining the informant.The research methods used are qualitative descriptive research methods.The results of the writing explain (1) the reason for the Social Relationship of brown sugar household production in Tanjuang Bungo Sub-District, Suliki District formed in the cooperative relationship that occurs between brown sugar employers and brown sugar processors, both in the process of working relations to their daily lives. The reason for the establishment of a cooperative relationship between employer and laborer is because the palm raw materials are starting to run low and the market demand is not fulfilled so that the production of palm sugar is turned into brown sugar made from granulated sugar. Granulated sugar which is capitalized to workers in the form of debt and is processed by workers into brown sugar and brown sugar will be accommodated by the employer. (2) Relationship of Production of Brown Sugar there is an imbalance, in which the employer controls the power of workers with sugar and is bound to produce brown sugar. The face to face that is often done by employers and workers in the production of brown sugar, such as when distributing sugar to workers, makes their relationship not limited to work relations but already considers like a family. And there is a form of empathy carried out between tokens and laborers. Keywords: social relations, Patron client, household industry.